Polymer-crystalline structures of cutoff type with homogeneous layers of high refraction index - Belayeva, A.I.; Kolomiets, S.N. (Functional Materials, 2004)
Effect of design parameters on characteristics of cutoff and band polymer-crystalline systems with layers thickness divisible by λ/4 has been studied in detail. The polymer-germanium systems have been shown to be of the greatest practical interest. A method has been developed to smooth the secondary extremes in the transparence band of a quarterwave polymer-germanium cutoff filter by introduction of additional interference layers made of polyethylene. The possibility to form a band type spectral characteristic has been shown in experiment for polymer-germanium systems in far IR spectral region.